An investigation into the perceptions of the first year mathematics students towards the alternative mode intervention : UNAM case study,Investigation into the perceptions of the first year mathematics students towards the alternative mode intervention : University of Namibia case study - Iipinge, Reginald Kaleke (Rhodes University, Faculty of Education, Department of Education, 2013)
A number of tertiary institutions offer bridging courses and intervention programmes in order to increase the number of students performing well in first year mathematics. At the university of Namibia, the science faculty provides educational opportunities to students who have not met the requirements to proceed with MAT 3511 (Basic Math). Unfortunately, the majority of students are not able to cope with the first year modules in Mathematics and the pass rates are unacceptably low. In the interest of supporting students, the University was prompted to introduce a two mode intervention programme in first year mathematics, namely: the normal mode and the alternative mode intervention. The alternative mode intervention was designed to improve the mathematics achievement of first year students who are considered low achieving or at risk of failure. This programme involves the identification of the lowest attainers in first year mathematics, and the provision of professional and faculty trained tutors and individualized teaching to these students in order to advance them to a level at which they are likely to learn successfully in a normal mode system. This research explores the experience and perceptions of first year students on the alternative mode, in particular as it relates to mathematical strands of proficiency. A second step was to explore how teaching contributes to the learning of mathematics on the intervention programme. The empirical investigation was done in 4 phases. A questionnaire on mathematics teaching and learning was given to the students during the first phase. During the second phase, two focus group discussions were conducted. Thereafter four interviews were carried out with lecturers, and finally tutorial and lecture observation were conducted. An analysis of these findings led to the identification of the students' experiences on the alternative mode. Analysis of the results indicate that the students identified mathematical proficiency as the central element to their learning, and pedagogical knowledge and exploratory talk were critical aspects of good teaching in the mathematical intervention programme.
Keywords: University of-- Namibia; Mathematics -- Study and teaching (Higher) -- Namibia; Compensatory education -- Namibia; Academic achievement -- Namibia; Education, Higher -- Namibia